Comparison of anti‐mutated citrullinated vimentin, anti‐cyclic citrullinated peptides, anti‐glucose‐6‐phosphate isomerase and anti‐keratin antibodies and rheumatoid factor in the diagnosis of rheumatoid arthritis in Chinese patients. (5th February 2013) - Zhu, Tao; Feng, Liyun
Abstract Aim To evaluate the diagnostic value of anti‐mutated citrullinated vimentin antibodies (anti‐MCV), anti‐cyclic citrullinated peptides antibodies (anti‐CCP), anti‐glucose‐6‐phosphate isomerase antibodies (anti‐GPI) and anti‐keratin antibodies (AKA) and rheumatoid factor (RF) in rheumatoid arthritis (RA). Methods The five auto‐antibodies were detected in serum samples of 56 patients with RA, 21 patients with systemic lupus erythematosus (SLE), 11 with ankylosing spondylitis (AS), six with Sjögren's syndrome (SS), four with connective tissue disease (CTD) and 20 healthy controls. Anti‐MCV, anti‐CCP and anti‐GPI were detected by enzyme‐linked immunosorbent assays (ELISA), AKA was determined by indirect immunofluorescence and RF was determined by rate nephelometry. Results In RA, anti‐MCV and anti‐GPI had the highest sensitivity (78.6% and 75.0%, respectively), anti‐CCP and AKA had the highest specificity (97.6%). Anti‐GPI had the lowest specificity (64.3%), and AKA had the lowest sensitivity (48.2%). When two antibodies were detected together, the sensitivity of anti‐MCV/anti‐CCP/RF were highest (92.9%) with a lower specificity (73.8%). The combination of anti‐MCV/anti‐CCP had a slightly decreased sensitivity (89.3%) and the same specificity (73.8%). Conclusions The combination RF/anti‐MCV/anti‐CCP or anti‐MCV/anti‐CCP are usefully serologic tests for the diagnosis of RA in Chinese patients.